2012
DOI: 10.1149/2.013302jes
|View full text |Cite
|
Sign up to set email alerts
|

A Phenomenological Degradation Model for Cyclic Aging of Lithium Ion Cell Materials

Abstract: A phenomenological Li-ion cell degradation model, pertaining to charge-discharge cyclic fatigue, is proposed and validated. It is known that Solid Electrolyte Inter-phase (SEI) formation on the particle surfaces consumes active Li leading to capacity loss. The problem is further aggravated by the creation of fresh surfaces by the fracture that develops as a result of intercalation induced stresses. In addition, fracture could result in isolation of chunks of electrode material or SEI could electronically isola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 83 publications
(148 reference statements)
1
47
0
Order By: Relevance
“…The diffevol algorithm is the Maple implementation of DE innovated by Storn and Price [17,18]. While traditional optimization methods such as the quasi-newton method requires the optimization problem to be differentiable, DE does not use the gradient function of the problem being optimized and therefore is more suitable for optimization problems that are variable, noisy and non-continuous.…”
Section: Optimisation Strategymentioning
confidence: 99%
See 2 more Smart Citations
“…The diffevol algorithm is the Maple implementation of DE innovated by Storn and Price [17,18]. While traditional optimization methods such as the quasi-newton method requires the optimization problem to be differentiable, DE does not use the gradient function of the problem being optimized and therefore is more suitable for optimization problems that are variable, noisy and non-continuous.…”
Section: Optimisation Strategymentioning
confidence: 99%
“…An important contribution to parameter identification was made by Forman et al [15] who identified the full set of parameters (88 scalars and function control points) of the P2D model using a genetic algorithm derived from the drive-cycle data from a plug-in hybrid electric vehicle (PHEV). In the context of battery degradation, perturbative terms have been introduced into the SP model and then identification used to obtain values of these perturbative parameters [16,17]. In the case of well-understood ageing mechanisms such as film formation on the negative electrode where models of degradation already exist, as was considered in [16,17], this approach is suitable.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Coupling of mechanical and chemical degradation using ROMs has been conducted to investigate the enhancement in capacity fade due to SEI growth on microcracks located on active particle surfaces.…”
Section: 54mentioning
confidence: 99%
“…12 Crack propagation, rupture, and isolation of portions of active particles can also cause loss of active sites where lithium atoms can intercalate, resulting in effective capacity fade. 13 In the past two to three decades, capacity fade due to the formation of SEI 8,10,[14][15][16][17] and lithium plating 18,19 have been investigated thoroughly. On the other hand, resistance growth and capacity fade due to delamination and site loss have not been explored extensively.…”
mentioning
confidence: 99%